Influence of an energy deficient and low carbohydrate acute dietary manipulation on iron regulation in young females - Hayashi N; Ishibashi A; Iwata A; Yatsutani H; Badenhorst C; Goto K (Wiley Periodicals LLC on behalf of The Physiological Society and the American Physiological Society, 2022)
Hepcidin is a liver-derived hormone that regulates iron metabolism. Recent studies suggest that an energy-deficient diet or low carbohydrate (CHO) availability may increase hepcidin in the absence of inflammation. The purpose of the present study was to examine the impact of either an energy-deficient diet or an ED diet with low CHO intake during three consecutive days on hepcidin responses, hematological variables, and energy metabolism in young Japanese women. Twenty-two young females were divided into two different groups, either an energy-deficient with low CHO intake group (ED + LCHO; 2.0 ± 0.3 g/kg/day CHO, 39%CHO, 1123 kcal/day) or an energy deficient with moderate CHO intake group (ED; 3.4 ± 0.3 g/kg/day CHO, 63%CHO, 1162 kcal/day). During the three consecutive days of the dietary intervention program, participants consumed only the prescribed diet and maintained their habitual physical activity levels. Body composition, substrate oxidation, iron metabolism, and inflammation were evaluated pre- and post-intervention. Serum iron and ferritin levels were significantly elevated following the intervention (p < 0.001, p = 0.003, respectively). Plasma interleukin-6 (IL-6) levels did not change following the intervention. Serum hepcidin levels significantly increased after the intervention (p = 0.002). Relative change in hepcidin levels was significantly higher in the ED + LCHO (264.3 ± 87.2%) than in the ED group (68.9 ± 22.1%, p = 0.048). Three consecutive days of an energy-deficient diet increased fasting hepcidin levels. Moreover, elevated hepcidin levels were further augmented when an energy-deficient diet was combined with a lower CHO intake.
© 2022 The Authors
Keywords: hepcidin; iron status; low carbohydrate availability; low energy availability; Diet; Dietary Carbohydrates; Female; Hepcidins; Humans; Inflammation; Iron